Short‐term hybridisation activates Tnt1 and Tto1 Copia retrotransposons in wild tuber‐bearing Solanum species - Paz, Rosalia Cristina; Rendina González, Alejandra Pilar; Ferrer, M.S.; Masuelli, Ricardo Williams (2018)
Interspecific hybridisation in tuber‐bearing species of Solanum is a common phenomenon and represents an important source of variability, crucial for adaptation and speciation of potato species. In this regard, the effects of interspecific hybridisation on retrotransposon families present in the genomes, and their consequent effects on generation of genetic variability in wild tuber‐bearing Solanum species, are poorly characterised. The aim of this study was to analyse the activity of retrotransposons in inter‐ and intraspecific hybrids between S. kurtzianum and S. microdontum, obtained by controlled crosses, and the effects on morphological, genetic and epigenetic variability. For genetic and epigenetic analysis, S‐SAP (sequence‐specific amplification polymorphism) and TMD (transposon methylation display) techniques were used, respectively, with specific primers for Tnt1 and Tto1 retrotransposon families (Order LTR, Superfamily Copia). The results indicate that at morphological level, interspecific hybrid genotypes differ from their parental species, whereas derived intraspecific hybrids do not. In both cases, we observed significant reductions in pollen grain viability, and a negative correlation with Tnt1 mobility. Both retrotransposons, Tto1 and Tnt1, were mobilised in the genotypes analysed, with mobility ranging from 0 to 7.8%. Furthermore, at the epigenetic level, demethylation was detected in the vicinity of Tnt1 and Tto1 in the hybrids compared with the parental genotypes. These patterns were positively correlated with the activity of the retrotransposons. The results suggest a possible mechanism through which hybridisation events generate genetic variability in tuber‐bearing species of Solanum through retrotranposon activation.